2018
DOI: 10.4048/jbc.2018.21.e61
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Immunoglobulin Mucin 3 Expression on Tumor Infiltrating Lymphocytes as a Positive Prognosticator in Triple-Negative Breast Cancer

Abstract: PurposeT-cell immunoglobulin and mucin domain-containing molecule 3 (TIM-3) is an emerging immune response molecule related to T-cell anergy. There has been tremendous interest in breast cancer targeting immune checkpoint molecules, especially in the triple-negative breast cancer (TNBC). This study was designed to investigate TIM-3 expression on tumor infiltrating lymphocytes (TILs), its relationships with clinicopathological para-meters and expression of programmed death receptor 1 (PD-1)/programmed death rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…It was reassuring that high‐level expression of TIM‐3 may be a general poor prognostic biomarker in osteosarcoma, gastric cancer, liver cancer, esophageal cancer and lymphoma. Although some findings suggested that high TIM‐3 expression indicated longer OS in breast cancer (HR = 0.11, 95% CI: 0.03‐0.39) 5 and renal cell carcinoma (HR = 0.54, 95% CI: 0.25‐1.17), 6 we found no relationship between TIM‐3 and breast cancer/kidney cancer/lung cancer. The possible reasons might include: (a) the function of TIM‐3 may vary depending upon tumor stages; (b) due to the heterogeneous nature of cancer 4‐6,55 .…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…It was reassuring that high‐level expression of TIM‐3 may be a general poor prognostic biomarker in osteosarcoma, gastric cancer, liver cancer, esophageal cancer and lymphoma. Although some findings suggested that high TIM‐3 expression indicated longer OS in breast cancer (HR = 0.11, 95% CI: 0.03‐0.39) 5 and renal cell carcinoma (HR = 0.54, 95% CI: 0.25‐1.17), 6 we found no relationship between TIM‐3 and breast cancer/kidney cancer/lung cancer. The possible reasons might include: (a) the function of TIM‐3 may vary depending upon tumor stages; (b) due to the heterogeneous nature of cancer 4‐6,55 .…”
Section: Discussioncontrasting
confidence: 70%
“…As shown in Figure 1, the initial literature search obtained 2432 articles and a total of 33 studies, 4‐6,12‐18,26‐48 including 4223 patients were finally included after further examination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated by the analysis of KM-plotter database, although Tim-3 is associated with poor prognosis in total breast cancer patients, the prognostic significance is varied in different subtypes. [56] including 109 samples of TNBC [57]. We therefore speculate that the distribution of Tim-3 expression on tumour cells or immune cells might have different prognostic significance, and the major location of Tim-3 in certain types of cells in cancer might determine the prognostic outcomes, although advanced investigation would be required to unveil the paradox of the Tim-3 clinical significance in future.…”
Section: Discussionmentioning
confidence: 99%